Cerebral malaria induced by plasmodium falciparum: clinical features, pathogenesis, diagnosis, and treatment - Song, Xiaonan; Wei, Wei; Cheng, Weijia; Zhu, Huiyin; Wang, Wei; Dong, Haifeng; Li, Jian (Frontiers in Cellular and Infection Microbiology, 2022)
Cerebral malaria (CM) caused by Plasmodium falciparum is a fatal neurological complication of malaria, resulting in coma and death, and even survivors may suffer long-term neurological sequelae. In sub-Saharan Africa, CM occurs mainly in children under five years of age. Although intravenous artesunate is considered the preferred treatment for CM, the clinical efficacy is still far from satisfactory. The neurological damage induced by CM is irreversible and lethal, and it is therefore of great significance to unravel the exact etiology of CM, which may be beneficial for the effective management of this severe disease. Here, we review the clinical characteristics, pathogenesis, diagnosis, and clinical therapy of CM, with the aim of providing insights into the development of novel tools for improved CM treatments.